2002
DOI: 10.1097/00001756-200207020-00023
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of adult bone marrow stem cells into neuroprogenitor cells in vitro

Abstract: We found the expression of neurofilament was very low in undifferentiated human adult bone marrow mesenchymal stem cells (hMSCs), but its expression could be significantly induced after treatment with combination of growth factors. Approximately 16% of hMSCs differentiated into cells expressing neurofilament after treatment with a combination of FGF and RA, retinoic acid. We also examined the effect of five different cell culture substrates on the expression of neurofilament. One specific combination that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 19 publications
4
80
1
3
Order By: Relevance
“…Results from the present study demonstrated that some MSCs differentiated into excitable neuronal-like cells. Previous studies have confirmed that MSCs can be induced to express neural markers and exhibit a neuronal appearance under specific induction conditions [4][5][6][7][8]. However, a normal mature neuron is not only defined by these characteristics, but more importantly by electrophysiological properties and functional activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Results from the present study demonstrated that some MSCs differentiated into excitable neuronal-like cells. Previous studies have confirmed that MSCs can be induced to express neural markers and exhibit a neuronal appearance under specific induction conditions [4][5][6][7][8]. However, a normal mature neuron is not only defined by these characteristics, but more importantly by electrophysiological properties and functional activity.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, MSCs have been reported to differentiate into neural cells in vitro [4][5][6][7][8] through the use of various chemical inductors, as well as in vivo following implanta-tion into the brain and spinal cord [9][10][11][12][13][14]. However, differentiation under chemical induction, or in combination with cytokines, should be reconsidered.…”
mentioning
confidence: 99%
“…Many studies demonstrated the differentiation of human and mice MSCs to neuron-like cells following induction with BME, DMSO and BHA [34]- [40], which exhibited a neuron-like morphology for few hours after induction which is due to a breakdown of the actin cytoskeleton and a retraction of the cell edge [40]. Since BHA also contains the sulfhydryl group, it may be deduced that the neuron-like morphology adopted by the exposed mouse MSCs has the same mechanism and could be due to the disruption of F-actin and cytoskeleton reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…Original reports that bone marrow cells could differentiate towards Purkinje neurons were challenged by others, reporting that these cells were the result of fusion of donor cells with endogenous Purkinje neurons (Alvarez-Dolado et al, 2003;Weimann et al, 2003b). Next to these in vivo studies, several in vitro studies have shown that stem cells could be isolated out of bone marrow and that these stem cells were capable of transdifferentiation towards neural-like cells (Woodbury et al, 2000;SanchezRamos et al, 2000;Kohyama et al, 2001;Deng et al, 2001;Kabos et al, 2002;Jiang et al, 2003Jiang et al, , 2002Kim et al, 2002;Munoz-Elias et al, 2003;Rismanchi et al, 2003;Levy et al, 2003;Locatelli et al, 2003;Padovan et al, 2003;Dezawa et al, 2004;Tondreau et al, 2004;Magaki et al, 2005;Bossolasco et al, 2005). In some of these studies, bone marrow-derived cells were even capable of differentiation towards cells of the three different germinal layers (endoderm, mesoderm and ectoderm).…”
Section: Introductionmentioning
confidence: 99%